Mobility-aware adaptive tag selection strategy in ambient backscatter systems - Mengistu Abera Mulatu; Thembelihle Dlamini; Wiseman Nkosingiphile Nyembe; Zenzo Police Ncube; Asrat Mulatu Beyene (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
Ambient backscatter communication (AmBC) has emerged as a promising solution to enable ultra-low-power connectivity in large-scale internet of things (IoTs) and future 6G mobile networks. In this paper, we consider a mobility-aware AmBC system, where a mobile user equipped with a reader in teracts with multiple passive tags deployed in the coverage area of a base station (BS). To achieve high decoding reliability, an adaptive tag selection scheme is proposed based on received signal strength (RSS) and interference constraints. Here, we derive a closed-form expression of the outage probabilities of both the mobile user and tags taking into account the Rayleigh double-fading nature of backscatter links. Performance evaluation carried out through simulations vali dates the theoretical analysis based on various selected system parameters. The results obtained show that the proposed adaptive scheme significantly improves system reliability compared to fixed tag selection strategies, thus emphasizing the importance of mobility-aware and context-driven adaptation in mobile IoT scenarios such as smart transportation and aerial data collection.